IMPROVING STUDENTS' READING COMPREHENSION USING SMALL GROUP DISCUSSION - Sukirman Sukirman (JURNAL ASIMILASI PENDIDIKAN, 2024)
The objectives of this research are to describe: (1) How the use of small group discussion can improve students reading comprehension. This research was conducted in the VII A class at SMP IT AN-NUR Suralaga. This research used Quantitative research since the researcher aimed to gain deeper description about the implementation of small group discussion technique. Data collection by way of test,and observation. Data were analyzed using several procedures. The result of the research show that the use of small group discussions can improve students understanding of reading. In addition, small group discussions can be used to make the classroom situation more conducive.